Phyllanthus acidus (L.) Skeels (Pemanfaatan dan Bioaktivitasnya - Marina Silalahi; Anisa Anggraeni; Nabela Fikriyya (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Phyllanthus acidus (Phyllataceae) is an underutilized fruits tree (UFT) which has the potential to be developed both as food and traditional medicine. This study aims to explain botany, benefits and bioactivity of P. acidus. The research method is using online library research on Google Scholar using the keywords P. acidus, bioactivity and uses of P. acidus. Local Indonesian people have long been cultivating P. acidus in their yards which are used as food, vegetables and traditional medicine, but on the other hand they contain toxic compounds known as Dichapetalins. The fruits of P. acidus has sour taste, not broken, juicy, 1 cm in diameter, 6-8 lobes, angular, enlarged fruit, hard endocarp. The P. acidus fruit is traditionally used to treat various diseases such as inflammation, rheumatism, bronchitis, asthma, respiratory disorders, liver disease, gastric disorders and diabetes. The use of P. acidus as a traditional medicine is related to its bioactivity as an antioxidant, anti-diabetes mellitus, anti-microbial, hepatoprotective, analgesic, anti-cancer, and diuretic. The toxic dichapetalins cause adverse health effects in higher doses so their use needs to be strictly controlled.